Experimental study of a membrane-based dehumidification cooling system - Chen, Ziwei; Zhu, Jie; Bai, Hongyu; Yan, Yuying; Zhang, Lizhi (Elsevier, 2017)
Membrane-based liquid desiccant dehumidification has attracted increasing interests with elimination of solution droplets carryover problem. In this study, a membrane-based hybrid liquid desiccant dehumidification cooling system is developed, which is mainly composed of a dehumidifier, a regenerator and an evaporative cooler. The system is capable to remove latent load by the liquid desiccant dehumidification unit and simultaneously to handle sensible load with an evaporative cooling unit. This paper presents a performance evaluation study of the hybrid system with calcium chloride as liquid desiccant based on experimental data. Series of tests are conducted to identify influences of operating variables and conditions (i.e. desiccant solution concentration ratio, regeneration temperature, inlet air condition, etc.) on the system performance. The experimental results indicate that the system is viable for dehumidification cooling purpose. Furthermore, it is noteworthy that mass balance between the dehumidifier and regenerator should be achieved for system steady operation. Thermal COPth of 0.70 and 24 electrical COPel of 2.62 are achieved respectively under steady operating condition at CaCl2 concentration ratio of 36%.